Leishmaniasis Panamensis Masquerading as Myiasis and Sporotrichosis: A Clinical Pitfall - Peter G. Pavlidakey; Thy Huynh; Kristopher Michael McKay; Naveed Sami (Hindawi Limited, 2015)
We report a case of cutaneous leishmaniasis panamensis in nonendemic Costa Rica. A 19-year-old female presented with nonhealing, unilateral eruption of erythematous papules with superficial central ulceration in a sporotrichoid pattern on right upper arm and back. Given the clinical picture and geographic locale, the patient was initially diagnosed with myiasis or human botfly infestation; however, the sporotrichoid pattern of the bites is an unlikely finding in myiasis. Peripheral blood smear, Giemsa stain, and polymerase chain reaction (PCR) were consistent for Leishmania spp. Ulceration resolved with 20-day course of IV sodium stibogluconate.